2013
DOI: 10.1017/s0950268812003147
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus lineage 2 in Sardinian wild birds in 2012: a further threat to public health

Abstract: West Nile virus (WNV) strains belonging to lineage 2 were detected and isolated from the tissues of a goshawk and two carrion crows in Sardinia in August 2012. According to NS3 sequence analysis, the Sardinian isolates shared a high level of similarity with those of Italian lineage 2 strains which circulated in 2011 and with the homologous sequence of the 2004 Hungarian isolate. Following the human fatality reported in 2011 in Olbia, this study is the first to report the spread and enzootic circulation of WNV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In these regions, veterinary and entomological surveillance documented the circulation of WNV, with evidence of the widespread presence of WNV lineage 2 in Sardinia island [45,47]. …”
Section: Resultsmentioning
confidence: 99%
“…In these regions, veterinary and entomological surveillance documented the circulation of WNV, with evidence of the widespread presence of WNV lineage 2 in Sardinia island [45,47]. …”
Section: Resultsmentioning
confidence: 99%
“…However, this substitution appears not to have the same effect for some other North American bird species and an experimental study has shown that this substitution alone in European WNV strains does not necessarily lead to an increased virulence for susceptible European birds [84]. Papa et al [23] related the H 249 P NS3 substitution to the increased virulence of the lineage 2 WNV strain that caused the outbreak in humans in Greece in 2010 [106], but the role of this substitution in the virulence for birds is not clear, as lineage 2 strains that have caused mortalities in birds do not show this change [18,23,30]. Therefore, the presence of other genetic markers of virulence could be implicated [22,107].…”
Section: Pathogenesis In Birdsmentioning
confidence: 99%
“…Greek/Hungarian cluster was detected by entomological and veterinary surveillance in the island of Sardinia as well as in the Veneto and Friuli-Venezia Giulia regions in north-eastern Italy in areas where WNV lin1 was also circulating [20][21][22].…”
Section: Epidemiological Situation Of West Nile Virus Infection In Eumentioning
confidence: 99%